Patency of Branch Vessels After Pipeline Embolization: Comparison of Various Branches - Wu, Xinzhi; Tian, Zhongbin; Li, Wenqiang; Liu, Jian; Zhang, Yisen; Zhang, Ying; Zhou, Yangyang; Yang, Xinjian; Mu, Shiqing (Frontiers in Neurology, 2019)
Objective: Pipeline embolization devices (PEDs) are widely used to exclude intracranial aneurysms from their parent arteries. Side branches covered by PEDs, however, sometimes experience occlusion and related symptoms. Thus, predictors of branch occlusion and the patency and clinical outcomes of these branches are concerning. Methods: We conducted a retrospective review of consecutive patients who had been treated with PEDs in our institution during 2015–2018 to identify those in whom one or more branches were involved. Pretreatment and follow-up angiograms were assessed to determine patency of the involved branches. Demographic and clinical data, treatment strategies, and comorbidities were collected to investigate their relations with branch occlusion. Results: Altogether, 173 branches [24 (13.9%) occluded), 29 (16.8%) with diminished flow] in 126 patients were studied. Five patients (OphA involved) presented with blurred vision and 1 patient (ACA involved) presented with headache. None of the other patients had neurologic complications or clinical strokes related to branch occlusion. Multivariate analysis identified that small PED diameter [p = 0.003, odds ratio (OR) = 0.168], branches arising from the aneurysm (p = 0.004, OR = 6.614), and involvement of the anterior cerebral artery (ACA) (p < 0.001, OR = 25.656) significantly predicted branch occlusion. Conclusion: Branch occlusion rate after PED deployment was low and most occlusions was asymptomatic. Branches with rich collateral supply were more likely to occlude, especially the ACA. Smaller PED diameter, branches arising from the aneurysm, and ACA involvement were significant predictors of branch occlusion after PED treatment.